Media Edukasi Tari Piring Minangkabau Dalam Fotografi - Puteri Tsamarah Desyanti; Fauzan Aulia (Journal of Creative Student Research, 2023)
Tari Piring is a dance art from the cultural heritage of the Minangkabau tribe in West Sumatra. The design of educational media for Tari Piring aims to produce learning media as an additional literature study related to Tari Piring Minangkabau in photography. The problem encountered is the lack of learning media for Tari Piring  that contains traditional movements and the meaning of these movements based on print. Therefore, the photography in this design uses stop action and long exposure techniques to depict the movements of Tari Piring. To find solutions to these problems, the 4D method (Define, Design, Develop, and Disseminate) was used. This method begins with defining the problem through data analysis and processing, followed by media design, development of initial designs to the dissemination stage. The existence of this design will produce an educational media that can be used as a learning media and additional literature study of Tari Piring and supporting the preservation of cultural heritage by designing several supporting media such as motion graphics, posters, x- banners, photocards, calendars, tumblers and stickers